Financialization of Real Estate Assets: A Comprehensive Approach to Investment Portfolios through a Gender-Based Study - Antonio Martínez Raya; Alejandro Segura de la Cal; Ainhoa Rodríguez Oromendía (Buildings, 2023)
Financialization is a process within the global economy wherein financial markets have been gaining ground in recent years. And yet, whether it has a beneficial or detrimental impact is almost totally unstudied, notably in terms of market effects on the real estate sector. To probe more deeply into such a research issue, this study addresses how real estate’s financialization impacts asset distribution by analyzing investment attitudes based on verifiable data from the Spanish wealth tax return. Despite scarce previous literature in the field, the study focused on the gender aspect to highlight the importance of investment decisions concerning risk aversion and related issues through the empirical analysis of the investment portfolios of those taxpayers subject to wealth tax statements. The findings identified show that financialization can lead to the conversion of property assets into stock-related movable assets, and from more to less imbalance, respectively, in terms of the gender gap. The results obtained show a significant gendered difference concerning investment stocks, being thus out of alignment with the gender equity traditionally promoted by the Spanish government. This suggests that although most investment portfolios of real estate properties are based strictly on criteria of profitability, female investors need to be empowered because they could provide a better approach to an economic issue wherein aversion to risk can become a proper criterion of private investors, even when there are sudden macroeconomic changes.